Golexanolone reduces glial activation in the striatum and improves non-motor and some motor alterations in a rat model of Parkinson's disease - Izquierdo-Altarejos, Paula; Arenas, Yaiza M.; Martínez-García, Mar; Vázquez, Lola; Mincheva, Gergana; Doverskog, Magnus; Blackburn, Thomas P.; Bohnen, Nicolaas I.; Llansola, Marta; Felipo, Vicente (Frontiers in Aging Neuroscience, 2024)
Background Parkinson's disease (PD) affects more than 6 million people worldwide. Along with motor impairments, patients and animal models exhibiting PD symptoms also experience cognitive impairment, fatigue, anxiety, and depression. Currently, there are no drugs available for PD that alter the progression of the disease. A body of evidence suggests that increased GABA levels contribute to the reduced expression of tyrosine hydroxylase (TH) and accompanying behavioral deficits. TH expression may be restored by blocking GABAA receptors. We hypothesized that golexanolone (GR3027), a well-tolerated GABAA receptor-modulating steroid antagonist (GAMSA), may improve Parkinson's symptoms in a rat model of PD. Objectives The aims of this study were to assess whether golexanolone can ameliorate motor and non-motor symptoms in a rat model of PD and to identify some underlying mechanisms. Methods We used the unilateral 6-OHDA rat model of PD. The golexanolone treatment started 4 weeks after surgery. Motor symptoms were assessed using Motorater and CatWalk tests. We also analyzed fatigue (using a treadmill test), anhedonia (via the sucrose preference test), anxiety (with an open field test), and short-term memory (using a Y maze). Glial activation and key proteins involved in PD pathogenesis were analyzed using immunohistochemistry and Western blot. Results Rats with PD showed motor incoordination and impaired locomotor gait, increased fatigue, anxiety, depression, and impaired short-term memory. Golexanolone treatment led to improvements in motor incoordination, certain aspects of locomotor gait, fatigue, anxiety, depression, and short-term memory. Notably, golexanolone reduced the activation of microglia and astrocytes, mitigated TH loss at 5 weeks after surgery, and prevented the increase of α-synuclein levels at 10 weeks. Conclusions Golexanolone may be useful in improving both motor and non-motor symptoms that adversely affect the quality of life in PD patients, such as anxiety, depression, fatigue, motor coordination, locomotor gait, and certain cognitive alterations.